Healthcare professionals' perceptions of system preparedness during public health emergencies: a path analysis of mental health impacts - Huang, Runze; Ding, Xueting; Li, Anlong; Nie, Guodong; Cheng, Ling; Li, Yajing; Gao, Wei; Ge, Han; Zhang, Mingjun; Cheng, Huaidong (Frontiers in Public Health, 2025)
BackgroundThe easing of COVID-19 policies in China appears to have been inadequately prepared, leading to a profound shift in the mental wellbeing of healthcare professionals following the lifting of these measures. Our study aims to investigate the pathways underlying negative emotions experienced by healthcare professionals due to perceived inadequate system preparedness, aiming to enhance their mental health protection and facilitate more effective responses during future large-scale public health crises.MethodsA total of 826 healthcare professionals were enrolled. Depression symptoms, anxiety symptoms, perceived stress, resilience, perceived inadequate system preparedness were measured in our research.ResultsThe prevalence of depression and anxiety symptoms among healthcare professionals were 32.1 and 16.2%, respectively, during the concentrated outbreak of COVID-19 in China after easing policy. The chain mediation analysis reveals that perceived inadequate system preparedness significantly directly predicts depression or anxiety symptoms among healthcare professionals, indirectly through the mediating role of stress, as well as via the chain mediation of stress and resilience. However, it does not predict these symptoms through the mediator of resilience alone. Furthermore, contracting COVID-19 directly predicts depression symptoms.ConclusionsPerceived inadequate system preparedness can have a detrimental impact on negative emotions through various channels. When facing the potential outbreak of a large-scale public health event in the future, it is crucial to implement measures such as providing psychological counseling, increasing risk allowances, and ensuring an adequate supply of personal protective equipment to be better prepared. Additionally, psychosocial interventions should be implemented to enhance the resilience of healthcare professionals and safeguard the mental wellbeing of those infected with COVID-19, etc.